2017
DOI: 10.1088/1361-648x/aa6184
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric glass of spheroidal dipoles with impurities: polar nanoregions, response to applied electric field, and ergodicity breakdown

Abstract: Using molecular dynamics simulation, we study dipolar glass in crystals composed of slightly spheroidal, polar particles and spherical, apolar impurities between metal walls. We present physical pictures of ferroelectric glass, which have been observed in relaxors, mixed crystals (such as KCN KBr ), and polymers. Our systems undergo a diffuse transition in a wide temperature range, where we visualize polar nanoregions (PNRs) surrounded by impurities. In our simulation, the impurities form clusters and their sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…For the mechanism of such super-para-magnetic relaxors, the presence of DM interactions are suggested, which will give weak ferromagnetism perpendicular to the polarization of PNR [61]. In addition, the MD simulation showed that the addition of spherical apolar impurity to spheroidal polar particles produces PNR to show the typical behavior of relaxors [63]. This seems analogous to the formation of ferroelectric domains in LC nitroxide radical samples by an impurity effect (See Section 4.2).…”
Section: Proposed Mechanismmentioning
confidence: 89%
“…For the mechanism of such super-para-magnetic relaxors, the presence of DM interactions are suggested, which will give weak ferromagnetism perpendicular to the polarization of PNR [61]. In addition, the MD simulation showed that the addition of spherical apolar impurity to spheroidal polar particles produces PNR to show the typical behavior of relaxors [63]. This seems analogous to the formation of ferroelectric domains in LC nitroxide radical samples by an impurity effect (See Section 4.2).…”
Section: Proposed Mechanismmentioning
confidence: 89%
“…We also introduce a dipole moment to spheroid i in parallel to n i as µ i = µ 0 n i . Then the dipolar interaction is described as (43)…”
Section: [2]mentioning
confidence: 99%
“…Motion and Numerical Units. The numerical integration of particle positions and orientations is obtained by solving the equation of motion for uniaxial molecules (43,62,63), mr i = −∂U/∂r i and I(…”
Section: Equation Ofmentioning
confidence: 99%
See 2 more Smart Citations